Effect of Job Promotion on The Performance of Civil Servants AT The Regional Office of The Ministry of Religion of Banten Province Mediated By Job Satisfaction - Encep Saefullah (Publisher Cv. Inara, 2021)
This study aims to determine the direct effect of job promotion on employee performance and job satisfaction, the direct effect of job satisfaction on employee performance and the effect of job promotion on employee performance through job satisfaction as an intervening variable. Data collection was carried out by distributing questionnaires. This study used quantitative data analysis with SPSS version 23. The total population was 205 ASN employees in the Regional Office of the Ministry of Religion, Banten Province. Samples were collected using random sampling technique, which obtained 67 respondents. The results of this study indicated that Job Promotion had a direct influence on employee performance, Job Promotion had no direct effect on job satisfaction, Job Satisfaction had no direct effect on employee performance and the indirect effect of Job Promotion on Employee Performance through Job Satisfaction showed a smaller percentage compared with the percentage of direct effect. Keywords: Job Promotion, Employee Performance, Job Satisfaction